Estimating carbon storage of Eucalyptus urophylla vegetation in Mutis Timau Nature Reserve, East Nusa Tenggara, Indonesia using remote sensing analysis - RONGGO SADONO; WAHYU WARDHANA; PANDU YUDHA ADI PUTRA WIRABUANA (Society for Indonesian Biodiversity, 2023)
Abstract. Sadono R, Wardhana W, Wirabuana PYAP. 2023. Estimating carbon storage of Eucalyptus urophylla vegetation in Mutis Timau Nature Reserve, East Nusa Tenggara, Indonesia using remote sensing analysis. Biodiversitas 24: 1946-1952. The presence of Eucalyptus urophylla S.T. Blake in Mutis Timau Nature Reserve (Cagar Alam) in Timor Island, East Nusa Tenggara Province, Indonesia plays an important role in long-term climate change mitigation. Therefore, this study aimed to investigate the carbon storage of E. urophylla in Mutis Timau Nature Reserve in varying tree densities using remote sensing analysis. Sentinel 2B satellite image acquired on 10 September 2022 was used to generate the Normalized Difference Vegetation Index (NDVI) using ArcGis 10.8. The NDVI values were then classified to generate the land cover type and density of E. urophylla. The NDVI values greater than 0.7 were assigned as the stands of E. urophylla and classified into low, moderate, and high density. The total carbon storage of each density area was calculated using the estimated area and secondary data of total carbon storage per ha for corresponding densities. The results of remote sensing analysis showed that E. urophylla vegetation was found to cover 73.82% or 9,084.56 ha of the total 12,306.43 ha estimated study area. The estimated area for moderate vegetation density of E. urophylla was 5,150.26 ha followed by low and high densities of 3,857.48 ha and 96.81 ha, respectively. The carbon storage of low, moderate, and high density was calculated to be 577,273.38, 996,655.61 and 27,467.90 tons C, respectively, totaling 1,601,396.89 tons C across the nature reserve. The findings of this study recommend that the coverage of E. urophylla vegetation needs to be expanded, specifically to become high-density to enhance carbon stock, for example through restoration.